Economic Growth Targets, Innovation Transformation, and Urban Carbon Emissions: An Empirical Study of the Yangtze River Delta - Dongsheng Yan; Ningru Wang; Yimeng Guo; Xiangwanchen Wang; Wei Sun (Land)
In the face of carbon emissions reduction efforts, which are a common but differentiated global responsibility, it is crucial to explore the potential synergistic path between economic growth and carbon emissions reduction. This study integrates economic growth management and carbon emissions into a theoretical framework, based on city-level panel data from 2005 to 2019 in the Yangtze River Delta and the fixed effects model. We explore the impact of economic growth targets on urban carbon emissions. Then, we explore the mechanism by which economic growth target affects carbon emissions with the mediation effect model and moderation effect model. The results reveal that economic growth targets are beneficial for carbon reduction, and innovation development from innovation transformation is an important mechanism driving carbon emissions reduction, but the effects of different innovation outputs exhibit notable variations. In addition, marketization and industrial structure affect the relationship between economic growth targets and carbon emissions. The heterogeneity analysis reveals substantial spatial and temporal differences. Based on the realities of developing countries’ ongoing economic targets, this study provides a new explanation for the relationship between government policies and carbon emissions, establishing a scientific basis for policymakers to formulate strategic green development policies.